Recombinant Factor C as an In Vitro Assay for the Residual Pathogenicity Evaluation of Veterinary Autogenous Vaccines - Antonella Di Paolo; Rosario Liberti; Lucia Anzalone; Claudia Colabella; Andrea Felici; Giulio Severi; Monica Cagiola (Veterinary Sciences)
Background: Veterinary autogenous vaccines, similar to all injectable pharmaceutical products, must be tested to assess endotoxin concentrations. The Limulus Amebocyte Lysate Test (LAL test) is widely used in in vitro quality control assays for endotoxin detection, although it presents some ethical issues related to the production of reagents and is also characterized by a low specificity due to other contaminants that can activate the reaction. For all these reasons, a new recombinant factor C LAL test was developed. Aim: In this study, we described the comparison between two LAL test methods for in vitro quality control of veterinary autogenous vaccines, with the aim of evaluating the most suitable method and establishing an endotoxin concentration range for two different matrices. Methods: Two hundred batches of two different vaccine matrices were tested using the kinetic chromogenic LAL test and recombinant factor C endotoxin detection assay commercial kits. Results and Conclusions: Statistical analysis conducted after the validation of the recombinant factor C test exhibited a statistically significant correlation between the two methods and for both vaccine matrices, suggesting that the animal-free assay can be used as a routine quality control test for veterinary autogenous vaccines.